Alpha + beta type easy-to-form high-strength titanium alloy containing active eutectoid elements and preparation method

By adding active euthanizing element copper to the titanium alloy to form nanoTi2Cu compounds, combined with solid solution and aging treatment, the problems of titanium alloy molding performance and microstructure regulation are solved, and high strength, high plasticity and easy-to-form α+ Beta-type titanium alloy, suitable for a variety of engineering applications.

CN119307780APending Publication Date: 2025-01-14INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411337785.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing titanium alloy materials have narrow hot processing windows, making it difficult to perform cold forming or temperature forming. The plasticity of the matrix decreases sharply after adding elements such as B and Si, resulting in increased engineering difficulty and difficulty in regulating strength and microstructure.

Method used

By adding active euthanizing copper, nano-Ti2Cu compounds are formed, and their precipitation ratio is regulated. Combined with optimized solid solution and aging treatment, a multi-scale composite structure is formed to improve the molding performance and strength of titanium alloys.

Benefits of technology

It has achieved the improvement of the forming performance of titanium alloys, expanded the window of thermal processing technology, reduced processing costs, and was suitable for aerospace and other fields under the premise of ensuring high strength and high plasticity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307780A_ABST
    Figure CN119307780A_ABST
Patent Text Reader

Abstract

The invention relates to the field of titanium alloy materials, in particular to an alpha + beta type easy-to-form high-strength titanium alloy containing active eutectoid elements and a preparation method. The titanium alloy comprises the following chemical components in percentage by mass: 5.0%-7.0% of an Al element, 2.0%-4.0% of an Nb element, 1.0%-3.0% of a Mo element, 1.0%-3.0% of a V element, 1.0%-2.0% of a Zr element, 3.0%-6.0% of a Cu element and the balance of Ti. Alpha + beta type easy-to-form high-strength titanium alloys with different strength levels are obtained according to the content of the Cu element, a nano Ti2Cu compound is rapidly formed at the eutectoid temperature by adding a high-activity eutectoid beta stable element Cu, the precipitation proportion of Ti2Cu is regulated and controlled by adjusting the content of Cu, and then the strength of the titanium alloy is regulated and controlled. The method can be widely applied to the important fields of aerospace, ocean engineering, weaponry, petrochemical engineering, automobile industry, biomedical treatment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of titanium alloy materials, and in particular to an α+β type easy-to-form high-strength titanium alloy containing active eutectoid elements and a preparation method thereof. Background Art

[0002] Titanium alloys are widely used in important fields such as aerospace, marine engineering, weapons and equipment, petrochemicals, automobile industry, and biomedicine due to their excellent specific strength, high corrosion resistance, and good high temperature resistance. With the increasing demand for equipment upgrades in the fields of aerospace, marine engineering, and weapons and equipment, higher requirements are placed on the forming performance of structural titanium alloy materials. However, the existing titanium alloy materials have a narrow hot working window, and the final rolling or final forging temperature needs to be strictly controlled, otherwise it is easy to cause cracks on the surface of the titanium alloy, which reduces the hot forming performance of the titanium alloy. At the same time, its yield strength ratio is generally high, and it is not easy to perform cold forming or warm forming. According to the Hall-Petch effect, the purpose of simultaneously improving strength and plasticity can be achieved by refining the grain size. However, titanium alloys usually add elements such as B and Si to refine the grains. The increase in the content of B and Si can easily cause a sharp drop in the plasticity of the matrix. The amount of the active eutectoid element Cu can be adjusted in a large range, and nano-Ti2Cu compounds can be generated, but the problem of element segregation during the smelting process increases the difficulty of engineering. Therefore, adding active eutectoid element copper to adjust the strength and fine microstructure of titanium alloy while solving the Cu segregation problem is of great significance for the research and development of easy-to-form high-strength titanium alloy. Summary of the invention

[0003] In view of the development trend and urgent demand for light weight, high strength and high toughness of new structural materials, the purpose of the present invention is to provide an α+β type easy-to-form high-strength titanium alloy (Ti15) containing active eutectoid elements and a preparation method thereof, so as to improve the forming performance of the structural titanium alloy while ensuring the high strength and high plasticity of the titanium alloy, thereby realizing the engineering application of the new material.

[0004] In order to achieve the above object, the technical solution of the present invention is:

[0005] The invention discloses an α+β type easy-to-form high-strength titanium alloy containing active eutectoid elements. The chemical composition of the titanium alloy is as follows by mass percentage: 5.0% to 7.0% Al element, 2.0% to 4.0% Nb element, 1.0% to 3.0% Mo element, 1.0% to 3.0% V element, 1.0% to 2.0% Zr element, 3.0% to 6.0% Cu element, and the balance is Ti. According to the content of Cu element, an α+β type easy-to-form high-strength titanium alloy with different strength levels is obtained. By adding a strongly active eutectoid β-stabilizing element Cu, a nano Ti2Cu compound is quickly formed at the eutectoid temperature. By adjusting the Cu content, the precipitation ratio of Ti2Cu is regulated, thereby regulating the strength of the titanium alloy.

[0006] The molybdenum equivalent range of the α+β type easy-to-form high-strength titanium alloy containing active eutectoid elements is 8-10.

[0007] The α+β type easy-to-form high-strength titanium alloy containing active eutectoid elements has the following chemical compositions by mass percentage: 6.3% to 6.8% Al element, 2.0% to 2.5% Nb element, 2.0% to 2.5% Mo element, 2.0% to 2.5% V element, 1.5% to 2.0% Zr element, 2.5% to 3.0% Cu element, and the remainder is Ti.

[0008] The α+β type easy-to-form high-strength titanium alloy containing active eutectoid elements has the following chemical compositions by mass percentage: 6.3% to 6.8% Al element, 2.0% to 2.5% Nb element, 2.0% to 2.5% Mo element, 2.0% to 2.5% V element, 1.0% to 1.5% Zr element, 3.8% to 4.3% Cu element, and the remainder is Ti.

[0009] The α+β type easy-to-form high-strength titanium alloy containing active eutectoid elements has the following chemical compositions by mass percentage: 6.3% to 6.8% Al element, 2.0% to 2.5% Nb element, 2.0% to 2.5% Mo element, 2.0% to 2.5% V element, 1.0% to 1.5% Zr element, 4.5% to 5.0% Cu element, and the remainder is Ti.

[0010] The preparation method of the α+β type easy-to-form high-strength titanium alloy containing active eutectoid elements comprises the following specific steps:

[0011] (1) Pressing electrode

[0012] Using titanium sponge, Al bean, AlV master alloy, AlMo master alloy, TiNb master alloy, TiCu master alloy and zirconium sponge as raw materials, the materials are prepared according to the alloy design composition and pressed into electrodes;

[0013] (2) Preparation of ingots

[0014] The electrode obtained in step (1) is used to perform vacuum consumable smelting three times to obtain an ingot;

[0015] (3) High temperature homogenization treatment

[0016] The qualified ingot obtained in step (2) is subjected to high temperature homogenization treatment at a temperature of T β +200℃, insulation time 12~24h;

[0017] (4) Forging

[0018] The ingot after step (3) is forged into a rod blank, and the blank forging temperature T β +200℃, single phase forging temperature T β +80℃, two-phase forging temperature T β -50℃, finished product forging temperature T β -80℃, the holding time of each forging process is 4 to 8h, and the final forging temperature is not less than 800℃;

[0019] (5) Rolling

[0020] The bar blank obtained in step (4) is rolled into a bar stock at a temperature T β The first hot rolling is carried out at -120℃, and the rolling deformation is 70-80%; at temperature T β The second hot rolling is carried out at -150℃, and the holding time is 2 to 6 hours;

[0021] (6) Solution treatment

[0022] The bar obtained in step (5) is kept in the two-phase region for water-cooling solid solution treatment at a holding temperature of T β -30~50℃, keep warm for 30min~1h, quickly cool to room temperature, and control the cooling rate between 25~200℃ / s;

[0023] (7) Aging treatment

[0024] The solid solution rod blank obtained in step (6) is subjected to aging treatment at a holding temperature of 450°C to 600°C for 4 to 24 hours, and then air-cooled to room temperature. α+β type easy-to-form high-strength titanium alloys of different strength levels can be obtained according to the content of Cu element.

[0025] In the preparation method of the α+β type easy-to-form high-strength titanium alloy containing active eutectoid elements, in step (2), the ingot is required to be melted uniformly using a small current density to prevent segregation of copper elements; after peeling, acoustic flaw detection is performed, and the riser of the ingot is cut off, and the β transformation temperature is determined by metallographic method.

[0026] In the method for preparing the α+β type easy-to-form high-strength titanium alloy containing active eutectoid elements, in step (4), grinding treatment is performed after each sequence of forging to ensure that the deformation of each sequence of forging is 50% to 70%.

[0027] In the method for preparing the α+β type easy-to-form high-strength titanium alloy containing active eutectoid elements, in step (5), grinding treatment is performed after each rolling sequence, and peeling treatment is performed after the last rolling sequence.

[0028] The method for preparing the α+β type easy-to-form high-strength titanium alloy containing active eutectoid elements, in steps (6)-(7), the alloy is rapidly cooled by solid solution treatment to form equiaxed primary α phase and α″ The pearlite-like composite structure composed of martensite lamellar structure is aged at 500±5℃ to obtain a multi-scale composite structure titanium alloy with fine microstructure, and has the three-level fine structure microstructure characteristics of micron-scale and nano-scale α phase and nano-Ti2Cu phase. The three-level fine structure microstructure characteristics include: primary α p The size of the phase is between 2 and 5 μm, and the secondary α s The thickness of the phase is between 200 and 500 nm, as well as the nano-Ti2Cu phase.

[0029] The design concept of the present invention is:

[0030] Most high-strength and high-toughness titanium alloys use α+β two-phase alloys, and use the precipitation of α phase to strengthen the β phase matrix. The present invention adds active eutectoid elements to the new titanium alloy to quickly form Ti2Cu compounds at the eutectoid temperature. Since the modulus of Ti2Cu compounds is high, the alloy strength can be regulated by adjusting their content. By controlling the content of each element in the alloy and regulating the molybdenum equivalent, the alloy forms primary equiaxed α phase and α″ martensite phase with different contents after solution treatment, wherein Cu rapidly diffuses in titanium to form a nano-Ti2Cu precipitation phase, which hinders the growth of the martensite lamellae thickness and can simultaneously refine the grains and produce a very fine microstructure. The α ″ Martensite can reduce yield strength and is easy to form. The α″ martensite phase is then transformed into a micro-nano secondary α phase through annealing or aging treatment. This very fine structural microstructure makes the alloy have high strength and toughness. At the same time, the increase of Cu element can reduce the high-temperature rheological stress of the alloy, increase hardenability, expand the hot working process window, reduce the number of hot working passes, and reduce the hot working process cost. The alloy has good plastic forming ability above 700°C. In order to avoid the problem that low-melting-point copper is easily enriched in the liquid phase during the smelting process, the present invention adopts 0.25-1mm small-particle TiCu intermediate alloy, and adjusts the smelting parameters at the same time to form a small molten pool, reduce the solidification temperature gradient, shorten the dendrite spacing, and thus control the ingot segregation.

[0031] The advantages and beneficial effects of the present invention are:

[0032] 1. Different from the microstructure of existing engineering titanium alloys, the Ti15 titanium alloy provided by the present invention has three levels of very fine structural microstructure characteristics, with micron- and nano-scale α phases, primary α p The size of the phase is between 2 and 5 μm, and the secondary α s The thickness of the phase is between 200 and 500 nm, as well as the nano-Ti2Cu phase.

[0033] 2. The method of the present invention uses Cu element to replace the external B, Si and other grain-refining phases, which can improve the yield strength and tensile strength while ensuring the plasticity of the alloy, and further increase the service safety and reliability of the alloy while meeting the lightweight requirements of the components.

[0034] 3. The method of the present invention can be used to prepare titanium alloy bars, wires, plates, etc.

[0035] 4. The method of the present invention can be used to prepare titanium alloy (Ti15) that is easy to form, high-strength and high-toughness, which can be widely used in many important fields such as aerospace, marine engineering, weapon equipment, petrochemical industry, automobile industry and biomedicine. β The solution treatment is carried out at -30 to 50 ° C with a holding time of 30 min to 1 h. The nano-Ti2Cu compound is quickly formed, and the grains are refined to form a pearlite-like composite structure. The α ″ Martensite can reduce the yield strength and is easy to form. Aging at 450-600℃ for 4-24h and then air cooling to room temperature can simultaneously improve the strength of titanium alloy and maintain good plasticity to obtain α+β type easy-to-form high-strength titanium alloy with a strength level of 1500-1800MPa and an elongation greater than 5%.

[0036] 5. The Ti15 titanium alloy prepared by the method described in the present invention can reduce the c / a ratio of the titanium alloy due to the addition of Cu element, increase the slip system, have lower high-temperature flow stress, small hot forming resistance, and a larger hot processing window of the material, which can reduce the processing and manufacturing costs and expand the engineering application field of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is the XRD phase analysis spectrum in hot rolling state, solid solution state and solid solution aging state.

[0038] Figure 2 It is a multi-scale composite microstructure under solid solution aging state.

[0039] Figure 3 It is the stress-strain curve of easy-to-form high-strength titanium alloy in solid solution state and aging state.

[0040] Figure 4 The stress-strain curves of the easily formable high-strength titanium alloy at different temperatures. In the figure, the abscissa truestrain is the true strain (%), and the ordinate true stress is the true stress (MPa). DETAILED DESCRIPTION

[0041] In the specific implementation process, the present invention adopts an α+β type easy-to-form high-strength titanium alloy (Ti15) regulated by an active eutectoid element, adds 5wt% to 7wt% of Al element and 1.0wt% to 2.0wt% of Zr element, strengthens the α phase, not only improves the critical shear stress of α-Ti dislocation slip, but also enables the sliding of the column and the base surface to start at the same time, which can simultaneously improve the yield strength and fracture toughness of the alloy. Then, 1.0wt% to 3.0wt% of V, 1.0wt% to 3.0wt% of Mo and 2.0wt% to 4.0wt% of Nb, which are isomorphous β stabilizing elements, are added to reduce the martensitic transformation temperature, improve the stability of the β phase, enhance the critical induced stress of the martensitic phase transformation, exert the TRIP and TWIP effects of the titanium alloy, and improve the plasticity of the titanium alloy. Finally, by adding 3.0wt% to 6.0wt% Cu, a highly active β-stabilizing element, nano-Ti2Cu compounds are quickly formed. By adjusting the Cu content, the precipitation ratio of Ti2Cu is regulated, and then the alloy strength is regulated. According to the content of Cu element, α+β type easy-to-form high-strength titanium alloys with different strength levels can be obtained. With the optimized solid solution process, the alloy is rapidly cooled to form a pearlite-like composite structure composed of an equiaxed primary α phase and a finer martensite lamellar structure. At the same time, the precipitation of the Ti2Cu precipitate phase hinders the growth of the martensite lamellar thickness, which can simultaneously play a role in refining the grains and microstructure. The α obtained after rapid cooling ″ Martensite can reduce the yield strength and is easy to shape. After annealing or aging treatment, the yield strength of the titanium alloy is increased again to meet the service conditions. The addition of eutectoid element copper can greatly reduce the resistance to high-temperature deformation, increase hardenability, expand the hot working process window, reduce the number of hot working passes, and reduce the cost of hot working processes. In order to avoid the problem that low-melting-point copper is easily enriched in the liquid phase during the smelting process, the present invention uses 0.25-1mm small-particle TiCu intermediate alloys, and adjusts the smelting parameters at the same time to form a small molten pool, reduce the solidification temperature gradient, shorten the dendrite spacing, and thus control the segregation of the ingot.

[0042] In order to make the purpose, technical solution and effect of the present application clearer and more explicit, the present application is further described in detail below with reference to the accompanying drawings and examples.

[0043] The specific examples and comparative examples are used to illustrate and explain the present application, but should not be used to limit the scope of the present application. Examples 1 to 3 are alloys prepared by appropriately adjusting the element content and Mo equivalent according to the preparation steps in the invention content.

[0044] Embodiment 1:

[0045] This embodiment proposes an α+β type easy-to-form high-strength titanium alloy (Ti15-1) containing active eutectoid elements. The chemical composition and mass percentage of the titanium alloy are: Al element 6.5%, Nb element 2.0%, Mo element 2.0%, V element 2.0%, Zr element 1.5%, Cu element 3.0%, and the remainder is Ti; the molybdenum equivalent is 8, and the phase transition point test temperature is 940±5℃.

[0046] In this embodiment, the preparation steps of the α+β type easy-to-form high-strength titanium alloy (Ti15-3) containing active eutectoid elements are as follows:

[0047] (1) Pressing electrodes: Using titanium sponge, Al bean, AlV master alloy, AlMo master alloy, TiNb master alloy, TiCu master alloy, and zirconium sponge as raw materials, the ingredients are prepared according to the alloy design composition and pressed into electrodes.

[0048] (2) Preparation of ingots. The electrode obtained in step (1) is used for three vacuum consumable melting to obtain an ingot. The ingot casting requires a low current density (35-40 kA / m 2 ) is uniformly melted. After peeling, ultrasonic flaw detection is carried out, and the riser is cut off from the ingot. At the same time, the β transformation temperature is determined by metallographic method to be 940±5℃.

[0049] (3) High-temperature homogenization treatment: The qualified ingot obtained in step (2) is subjected to high-temperature homogenization treatment at a temperature of 1140° C. and a holding time of 24 h.

[0050] (4) Forging. The ingot treated in step (3) is forged into a billet, with a billet forging temperature of 1140±5°C and a holding time of 8h, a single-phase forging temperature of 1020±5°C and a holding time of 6h, a two-phase forging temperature of 890±5°C and a holding time of 5h, a finished product forging temperature of 860±5°C and a holding time of 4h, and a final forging temperature of not less than 800°C. Returning to the furnace is allowed no more than twice. Grinding is performed after each forging sequence to ensure that the deformation of each forging sequence is 60%.

[0051] (5) Rolling. The bar blank obtained in step (4) is subjected to the first hot rolling at a temperature of 820±5°C, with a rolling deformation of 75%; and the second hot rolling is carried out at a temperature of 790±5°C, with a holding time of 2h. After rolling, the bar blank is subjected to peeling and polishing.

[0052] (6) Heat treatment. The bar obtained in step (5) is subjected to water-cooling solid solution treatment at a temperature of 905°C for 1 hour to obtain an easily moldable high-strength titanium alloy with a tensile strength of 1250 MPa and a yield strength of 432 MPa. Aging is continued at 500±5°C for 4 hours, and then air-cooled to room temperature to obtain an ultra-high-strength titanium alloy with a tensile strength of 1568 MPa, a yield strength of 1426 MPa, an elongation of 9.5%, and a cross-sectional shrinkage of 35%.

[0053] Embodiment 2:

[0054] This embodiment proposes an α+β type easy-to-form high-strength titanium alloy (Ti15-2) containing active eutectoid elements. The chemical composition and mass percentage of the titanium alloy are: Al element 6.5%, Nb element 2.0%, Mo element 2.0%, V element 1.5%, Zr element 1.0%, Cu element 4.0%, and the remainder is T; the molybdenum equivalent is 9, and the phase transition point test temperature is 920±5℃.

[0055] In this embodiment, the preparation steps of the α+β type easy-to-form high-strength titanium alloy (Ti15-3) containing active eutectoid elements are as follows:

[0056] (1) Pressing electrodes: Using titanium sponge, Al bean, AlV master alloy, AlMo master alloy, TiNb master alloy, TiCu master alloy, and zirconium sponge as raw materials, the ingredients are prepared according to the alloy design composition and pressed into electrodes.

[0057] (2) Preparation of ingots. The electrode obtained in step (1) is used for three vacuum consumable melting to obtain an ingot. The ingot casting requires a low current density (35-40 kA / m 2 ) is uniformly melted. After peeling, ultrasonic flaw detection is carried out, and the riser is cut off from the ingot. At the same time, the β transformation temperature is determined by metallographic method to be 920±5℃.

[0058] (3) High-temperature homogenization treatment: The qualified ingot obtained in step (2) is subjected to high-temperature homogenization treatment at a temperature of 1120° C. and a holding time of 24 h.

[0059] (4) Forging. The ingot treated in step (3) is forged into a billet, with a billet forging temperature of 1120±5°C and a holding time of 8h, a single-phase forging temperature of 1005±5°C and a holding time of 6h, a two-phase forging temperature of 880±5°C and a holding time of 5h, a finished product forging temperature of 850±5°C and a holding time of 4h, and a final forging temperature of not less than 800°C. Returning to the furnace is allowed no more than twice. Grinding is performed after each forging sequence to ensure that the deformation of each forging sequence is 60%.

[0060] (5) Rolling. The bar blank obtained in step (4) is subjected to the first hot rolling at a temperature of 810±5°C, with a rolling deformation of 75%; the second hot rolling is carried out at a temperature of 780±5°C, with a holding time of 2h. After rolling, the bar blank is subjected to peeling and polishing.

[0061] (6) Heat treatment. The bar obtained in step (5) was subjected to water-cooling solid solution treatment at a temperature of 895°C for 1 hour to obtain an easily moldable high-strength titanium alloy with a tensile strength of 1231MPa and a yield strength of 358MPa. Aging was continued at 500±5°C for 4 hours, and then air-cooled to room temperature to obtain an ultra-high-strength titanium alloy with a tensile strength of 1619MPa, a yield strength of 1468MPa, an elongation of 7.0%, and a cross-sectional shrinkage of 36%.

[0062] Embodiment 3:

[0063] This embodiment proposes an α+β type easy-to-form high-strength titanium alloy (Ti15-3) containing active eutectoid elements. The chemical composition and mass percentage of the titanium alloy are: Al element 6.5%, Nb element 2.0%, Mo element 1.5%, V element 2%, Zr element 1.0%, Cu element 5.0%, and the remainder is Ti; the molybdenum equivalent is 10, and the phase transition point test temperature is 905±5℃.

[0064] In this embodiment, the preparation steps of the α+β type easy-to-form high-strength titanium alloy (Ti15-3) containing active eutectoid elements are as follows:

[0065] (1) Pressing electrodes: Using titanium sponge, Al bean, AlV master alloy, AlMo master alloy, TiNb master alloy, TiCu master alloy, and zirconium sponge as raw materials, the ingredients are prepared according to the alloy design composition and pressed into electrodes.

[0066] (2) Preparation of ingots. The electrode obtained in step (1) is used for three vacuum consumable melting to obtain an ingot. The ingot casting requires a low current density (35-40 kA / m 2 ) is uniformly melted. After peeling, ultrasonic flaw detection is carried out, and the riser is cut off from the ingot. At the same time, the β transformation temperature is determined by metallographic method to be 930±5℃.

[0067] (3) High-temperature homogenization treatment: The qualified ingot obtained in step (2) is subjected to high-temperature homogenization treatment at a temperature of 1120° C. and a holding time of 24 h.

[0068] (4) Forging. The ingot treated in step (3) is forged into a billet, with a billet forging temperature of 1120±5°C and a holding time of 8h, a single-phase forging temperature of 1005±5°C and a holding time of 6h, a two-phase forging temperature of 880±5°C and a holding time of 5h, a finished product forging temperature of 850±5°C and a holding time of 4h, and a final forging temperature of not less than 800°C. Returning to the furnace is allowed no more than twice. Grinding is performed after each forging sequence to ensure that the deformation of each forging sequence is 60%.

[0069] (5) Rolling. The bar blank obtained in step (4) is subjected to the first hot rolling at a temperature of 810±5°C, with a rolling deformation of 75%; the second hot rolling is carried out at a temperature of 780±5°C, with a holding time of 2h. After rolling, the bar blank is subjected to peeling and polishing.

[0070] (6) Heat treatment. The bar obtained in step (5) is subjected to water-cooling solid solution treatment at a temperature of 895±5°C for 1 hour to obtain an easily moldable high-strength titanium alloy with a tensile strength of 1234MPa and a yield strength of 365MPa. Aging is continued at 500±5°C for 4 hours, and then air-cooled to room temperature to obtain an ultra-high-strength titanium alloy with a tensile strength of 1796MPa, a yield strength of 1538MPa, an elongation of 5.0%, and a cross-sectional shrinkage of 11%.

[0071] See also Figures 1 to 4 .like Figure 1 As shown, the XRD phase analysis spectra in the hot-rolled state, solid solution state, and solid solution aging state in Example 1 of the present invention are as follows: Figure 1 It can be seen that a large amount of α″ and Ti2Cu are formed in the solid solution state. Figure 2 As shown, the multi-scale composite structure in the solid solution aging state in Example 1 of the present invention has very fine structural microstructural characteristics, and has both micron-scale and nano-scale α phases, primary α p The size of the phase is between 2 and 5 μm, and the secondary α s The width of the phase is between 200 and 500 nm, as well as the nano-Ti2Cu phase. Figure 3 As shown, the stress-strain curves of the easily formed high-strength titanium alloys with different element contents obtained after solution aging treatment in Examples 1, 2, and 3 of the present invention are shown in FIG. Figure 3 It can be seen that the tensile strength level is 1500MPa~1800MPa, and the elongation is 5%~10%. Figure 4 As shown, the stress-strain curves of the high-strength titanium alloy at different temperatures in Example 3 of the present invention are as follows: Figure 4 It can be seen that as the temperature increases, the flow stress of the alloy decreases. When the temperature reaches above 700°C, the stress is only below 189MPa and the strain reaches above 65%.

[0072] Table 2 Mechanical properties of Examples 1 to 3

[0073]

[0074] Table 3 High temperature mechanical properties of Example 3

[0075]

[0076] It can be seen from the results in Table 2 and Table 3 that the alloys in Examples 1 to 3 have high strength and good plasticity, and their yield strength in the solid solution state is relatively low, which is conducive to forming.

[0077] The results of the embodiments show that the addition of active eutectoid elements in the titanium alloy of the present invention is conducive to regulating the microstructure and improving the comprehensive mechanical properties. The active eutectoid elements include nickel, copper, silver, silicon, etc., among which Ni and Ag reduce the elastic modulus, and the plasticity of the material is greatly reduced after the Si content is increased. The general usage amount is no more than 0.5wt%, and the addition amount of Cu can be adjusted in a large range, and the modulus of the generated Ti2Cu is high, but because of the problem of element segregation during the smelting process, the engineering difficulty increases. The advantage of the present invention is to optimize the smelting process and the way of copper addition, and use a titanium-copper intermediate alloy to avoid the problem of low-melting-point copper being easily enriched in the liquid phase during the smelting process. At the same time, the smelting parameters are adjusted to form a small molten pool, reduce the solidification temperature gradient, shorten the dendrite spacing, and thus overcome local component segregation. Because the active eutectoid element copper can quickly form nano Ti2Cu compounds, the precipitation ratio of Ti2Cu is adjusted by adjusting the Cu content, and then the alloy strength is regulated. The present invention adjusts the internal microstructure of the microstructure by adjusting the proportion of the active eutectoid element copper, which can not only regulate the strength of the titanium alloy, but also ensure good plasticity. The present invention can be used to prepare an easy-to-form, high-strength, multi-scale composite structure titanium alloy with very fine structural microstructure characteristics, and at the same time, micron- and nano-scale α phases and nano Ti2Cu phases. The serviceability of the structural titanium alloy can be improved, and the process window of the titanium alloy material can be expanded, thereby realizing the engineering application of new materials.

[0078] The above description is only an implementation method of the present application, and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. An α+β type easily formed high-strength titanium alloy containing active eutectoid elements, characterized in that: The titanium alloy has the following chemical compositions by mass percentage: 5.0% to 7.0% Al, 2.0% to 4.0% Nb, 1.0% to 3.0% Mo, 1.0% to 3.0% V, 1.0% to 2.0% Zr, 3.0% to 6.0% Cu, and the balance is Ti. According to the content of Cu, an α+β type easy-to-form high-strength titanium alloy with different strength levels is obtained, and a strongly active eutectoid β-stabilizing element Cu is added to rapidly form a nano-Ti2Cu compound at a eutectoid temperature, and the precipitation ratio of Ti2Cu is regulated by adjusting the content of Cu, thereby regulating the strength of the titanium alloy.

2. The α+β type easily moldable high-strength titanium alloy containing active eutectoid elements according to claim 1, characterized in that: The molybdenum equivalent range is 8 to 10.

3. The α+β type easily moldable high-strength titanium alloy containing active eutectoid elements according to claim 1, characterized in that: Calculated by mass percentage, the chemical composition of the titanium alloy is: 6.3% to 6.8% Al element, 2.0% to 2.5% Nb element, 2.0% to 2.5% Mo element, 2.0% to 2.5% V element, 1.5% to 2.0% Zr element, 2.5% to 3.0% Cu element, and the balance is Ti.

4. The α+β type easily moldable high-strength titanium alloy containing active eutectoid elements according to claim 1, characterized in that: Calculated by mass percentage, the chemical composition of the titanium alloy is: 6.3% to 6.8% Al element, 2.0% to 2.5% Nb element, 2.0% to 2.5% Mo element, 2.0% to 2.5% V element, 1.0% to 1.5% Zr element, 3.8% to 4.3% Cu element, and the balance is Ti.

5. The α+β type easily moldable high-strength titanium alloy containing active eutectoid elements according to claim 1, characterized in that: Calculated by mass percentage, the chemical composition of the titanium alloy is: 6.3% to 6.8% Al element, 2.0% to 2.5% Nb element, 2.0% to 2.5% Mo element, 2.0% to 2.5% V element, 1.0% to 1.5% Zr element, 4.5% to 5.0% Cu element, and the balance is Ti.

6. A method for preparing the α+β type easily moldable high-strength titanium alloy containing active eutectoid elements according to any one of claims 1 to 5, characterized in that: The specific steps are as follows: (1) Pressing electrode Using titanium sponge, Al bean, AlV master alloy, AlMo master alloy, TiNb master alloy, TiCu master alloy and zirconium sponge as raw materials, the materials are prepared according to the alloy design composition and pressed into electrodes; (2) Preparation of ingots The electrode obtained in step (1) is used to perform vacuum consumable smelting three times to obtain an ingot; (3) High temperature homogenization treatment The qualified ingot obtained in step (2) is subjected to high temperature homogenization treatment at a temperature of T β +200℃, insulation time 12~24h; (4) Forging The ingot after step (3) is forged into a rod blank, and the blank forging temperature T β +200℃, single phase forging temperature T β +80℃, two-phase forging temperature T β -50℃, finished product forging temperature T β -80℃, the holding time of each forging process is 4 to 8h, and the final forging temperature is not less than 800℃; (5) Rolling The bar blank obtained in step (4) is rolled into a bar stock at a temperature T β The first hot rolling is carried out at -120℃, and the rolling deformation is 70-80%; at temperature T β The second hot rolling is carried out at -150℃, and the holding time is 2 to 6 hours; (6) Solution treatment The bar obtained in step (5) is kept in the two-phase region for water-cooling solid solution treatment at a holding temperature of T β -30~50℃, keep warm for 30min~1h, quickly cool to room temperature, and control the cooling rate between 25~200℃ / s; (7) Aging treatment The solid solution rod blank obtained in step (6) is subjected to aging treatment at a holding temperature of 450°C to 600°C for 4 to 24 hours, and then air-cooled to room temperature. α+β type easy-to-form high-strength titanium alloys of different strength levels can be obtained according to the content of Cu element.

7. The method for preparing the α+β type easily moldable high-strength titanium alloy containing active eutectoid elements according to claim 6, characterized in that: In step (2), the ingot is required to be melted uniformly with a small current density to prevent segregation of the copper element; after peeling, acoustic flaw detection is performed, and the riser of the ingot is cut off, and the β transformation temperature is determined by metallographic method.

8. The method for preparing the α+β type easily moldable high-strength titanium alloy containing active eutectoid elements according to claim 6, characterized in that: In step (4), grinding treatment is performed after each forging sequence to ensure that the deformation amount of each forging sequence is 50% to 70%.

9. The method for preparing the α+β type easily moldable high-strength titanium alloy containing active eutectoid elements according to claim 6, characterized in that: In step (5), grinding treatment is performed after each rolling sequence, and peeling treatment is performed after the last rolling sequence.

10. The method for preparing the α+β type easily moldable high-strength titanium alloy containing active eutectoid elements according to claim 6, characterized in that: In steps (6)-(7), the solution treatment causes the alloy to cool rapidly to form equiaxed primary α phase and α ″ The pearlite-like composite structure composed of martensite lamellar structure is aged at 500±5℃ to obtain a multi-scale composite structure titanium alloy with fine microstructure, and has the three-level fine structure microstructure characteristics of micron-scale and nano-scale α phase and nano-Ti2Cu phase. The three-level fine structure microstructure characteristics include: primary α p The size of the phase is between 2 and 5 μm, and the secondary α s The thickness of the phase is between 200 and 500 nm, as well as the nano-Ti2Cu phase.